Teatro - Villalba Arévalo, María Ximena (2018)
La Mariscal is located inside of a solid neighborhood, it is one of the 32 Quito urban parish. La Mariscal borders in North with Iñaquito, Northeast with Belisarius Quevedo, southeast with San Juan, south and east by Itchimbias parish. It is also part of Metropolitan District of Quito. After analyzing the area, problems in terms of mobility were identified since it does not have a universal accessibility and it is inside of an island. Therefore, it is noticed that it does not have a transversal connection, moreover, if there is a longitudinal connection, which directly connect the city from north to south. The existence of public space does not supply La Mariscals citizens, which lacks green spaces and some spaces have become vandalism and sanitary places, due to it, it needs to be rehabilitate to get better quality and adaption of users. Moreover, there are houses of Patrimonial value, which are neglected and decrease the interest of patrimonial character at the same time it degrades the perspective of the space. For this reason, consolidate the heritage house is necessary, protecting them and stand out the patrimonial character on the area. The equipment that belongs to La Mariscal is more than financial, commercial and service entities; it can be clearly shown that La Mariscal has become a place of work, and not in a recreational, leisure and social exchange place, so redistribution and the implementation of new equipment are necessary for the supply of users residing in La Mariscal with a projection for 2040. This new plan arises from centralities and micro-centers, which respond with activities belonging to each area of La Mariscal. 4 centralities and 3 micro-centers were planned, which are consolidated through clusters of equipment, public space, mobility, heritage and land use. Moreover, each of these has one intermodal that allows a better communication between facilities and a connectivity of both, La Mariscal Alta and La Mariscal Baja. The project developed for the certification work is: Zonal scale Theater; it is located in the centrality of cultural-recreational character, that belongs to B Zone, Border in the north by Eloy Alfaro Avenue, to the south by Av. Francisco de Orellana, to the east by La Pradera Street and to the west by the Av. Rio Amazonas. A cultural facility is proposed, in order to promote culture for La Mariscal users, where social, cultural and economic exchange exist. A Theater is planned for a projection to 2040 in order to supply the entire population of La Mariscal, also develop different multifunctional spaces to create different activities, which would activate as the place as the equipment, to become a point of attraction of institutions, education, commerce and service of the area. Finally, the project approach will be based from the urban planning plan, which was developed in the workshop AR0-960 of 2017, in order to satisfy the needs of inhabitant of La Mariscal with a vision for 2040. Finally, the project approach will be based from the Ordering Plan, which was developed in the workshop AR0-960 of 2017, in order to satisfy the needs of inhabitants of La Mariscal with a vision for 2040 and potentiate the place through by analyzing the area, to create something iconic inside of the area and at the same time to turn into a cultural, tourist and environmental attraction area.